Sensitivity Analysis of Revenue Potential in The Evaluation of East Surabaya Hospital Investment - Arianti Widi Astasari; Wateno Oetomo; Sajiyo Sajiyo (International Journal of Social Science and Community Service, 2024)
As one of the largest cities in Indonesia, the City of Surabaya has an obligation to provide excellent health services for its residents. It goes without saying that Surabaya City Government is required to provide a General Hospital that can receive referrals from the government-owned Community Health Centers. For this reason, the Surabaya City Government built the East Surabaya Hospital which is located in Rungkut Sub-District. East Surabaya Hospital is a strategic project that requires investment feasibility analysis. The East Surabaya Hospital investment feasibility analysis was done by applying the Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP) and Benefit Cost Ratio (BCR) parameters. After the feasibility analysis results were obtained, a sensitivity analysis was done on changes in management costs and the amount of health service levy rates for each Fees alternative. Based on the results of the investment feasibility analysis of 4 (four) Fees alternatives, there are 2 alternatives that can be concluded as worthy investments, which are alternative 1 and alternative 3. Meanwhile, alternative 2 and alternative 4 are not feasible since the NPV parameter shows negative values and the IRR value is lower than the MARR value. However, based on sensitivity analysis, alternatives 2 and 4 can be feasible if alternative 2’s service rate is increased by 13.2%, and alternative 4’s service rate is increased by 2.3%. The opposite applies in alternative 1 where the investment might become unfeasible if the service rate is reduced by more than 5.4% and alternative 3 might become unfeasible if the service rate is reduced by more than 2.5%.